Novel sp³ forms of carbon predicted by evolutionary metadynamics and analysis of their synthesizability using transition path sampling - Boulfelfel, S.E.; Zhu, Q.; Oganov, A.R. (Сверхтвердые материалы, 2012)
Experiments on cold compression of graphite have indicated the existence of a new superhard and transparent allotrope of carbon. Numerous metastable candidate structures featuring different topologies have been proposed for “superhard graphite”, showing a good agreement with experimental X-ray data. In order to determine the nature of this new allotrope, we use evolutionary metadynamics to systematically search for low-enthalpy sp³ carbon structures easily accessible from graphite and we employ molecular-dynamics transition path sampling to investigate the corresponding kinetic pathways starting from graphite at 15–20 GPa. Real transformation kinetics are computed and physically meaningful transition mechanisms are produced at the atomistic level of detail in order to demonstrate how nucleation mechanism and transformation kinetics lead to M-carbon as final product of cold compression of graphite. This establishes M-carbon as an experimentally synthesized carbon allotrope. Експерименти по холодному стисненню графіту показали наявність нової надтвердої і прозорою аллотропной форми вуглецю. Численні метастабільні структури з різною топологією були запропоновані для “надтвердого графіту” і показували добру відповідність експериментальним даним рентгенографії. Для однозначного визначення природи цієї нової аллотропной форми нами використано еволюційну метадінаміку, метод, що дозволяє систематичний пошук низькоентальпійних sp³-вуглецевих структур, що кінетично легко одержують з графіту, а також застосований молекулярно-динамічний вибір способів дослідження відповідної кінетики перетворення графіту при тисках 15–20 ГПа. Розрахована реальна кінетика перетворення графіту і отримані на атомистическому рівні реалістичні механізми перетворення, що демонструють, як механізм нуклеації та кінетика перетворення приводять до M-вуглецю – кінцевого продукту холодного стиснення графіту. Ці дослідження дозволяють вважати М-вуглець експериментально синтезованої алотропной формою вуглецю. Эксперименты по холодному сжатию графита показали наличие новой сверхтвердой и прозрачной аллотропной формы углерода. Многочисленные метастабильные структуры с различной топологией были предложены для “сверхтвердого графита” и показывали хорошее согласие с экспериментальными данными рентгенографии. Для однозначного определения природы этой новой аллотропной формы нами использована эволюционная метадинамика, метод, позволяющий систематический поиск низкоэнтальпийных sp³-углеродных структур, кинетически легко получаемых из графита, а также применен молекулярно-динамический выбор способов исследования соответствующей кинетики превращения графита при давлениях 15–20 ГПа. Рассчитана реальная кинетика преобразования графита и получены на атомистическом уровне реалистичные механизмы превращения, которые демонстрируют, как механизм нуклеации и кинетика превращения приводят к M-углероду – конечному продукту холодного сжатия графита Эти исследования позволяют считать М-углерод экспериментально синтезированной аллотропной формой углерода.